Mathematical model of detection of intra-erythrocyte pathologies using optoacoustic method - D. A. Kravchuk (Biomedical Photonics)
Malaria causes a serious health problem in the tropical and subtropical regions of the globe. In many cases, the consequences of this disease are fatal. Therefore, a simple, fast, accurate and affordable diagnostic system for the early detection of this disease is necessary for the timely administration of antimalarial drugs.The malarial parasite, during its intra-erythrocyte development, processes a significant amount of hemoglobin, which in this case turns into a hem form called hemozoin. Hemozoin and hemoglobin have different molar extinction coefficients at certain optical wavelengths, hence, light absorption and an optoacoustic signal (OAS) from the infected cell will be different from that of a healthy cell. The paper describes the developed theoretical model intended for studying the influence of intra-erythrocyte malarial parasite development on optoacoustic signals. The OAS were calculated based on the models of healthy and infected blood modeled on the basis of a 3D model.The simulated OAS were analyzed in the temporal and frequency domains to obtain signs of infection at various stages. The calculated OAS spectra have different amplitude levels, which indicates that the optoacoustic method can be useful for differentiating various intraerythrocyte stages of the malarial parasite. The carried out modeling and the results obtained allow us to continue working on the creation of an optoacoustic flow cytometer.